Onset of Feeding After Surgical Procedures in Newborns with Congenital Anomalies and Its Related Factors - Tabatabaei, SeyyedehNegin; Ghorban Sabagh, Vafa; Shariat, Mamak; Taghva Nakhjiri, Mobina; Ghavami Adel, Maryam (Iranian Journal of Pediatric Surgery, 2025)
Introduction: Congenital anomalies and related surgeries are common in neonates, especially in developing countries. In recent years, early feeding after surgery has become more popular. Postoperative care protocols should be updated to reflect these changes and improve outcomes. This study aimed to assess the onset of feeding after surgical procedures in newborns with congenital anomalies and its related factors. Material and Methods: This cross-sectional study was conducted on 90 neonates who underwent surgical procedures between 2011 and 2019 at Valiasr Hospital, Iran. The neonates’ demographics, including gender, weight, type of anomaly, presence or absence of heart disease, sepsis, prematurity, duration of surgery, volume of nasogastric tube secretions, time of defecation, and time of onset of feeding were recorded. The relationship between these factors and the early onset of feeding was analyzed in the neonates using the independent t-test, Kruskal-Wallis test, and logistic linear regression (P≤0.05). Results: A total of 90 neonates underwent surgical procedures during the specified period, of which 43% were female, 49% had heart disease, 46% had sepsis, and 34% were premature. The mean weight of the neonates was 2726.94 (806.19) grams. The mean time to the onset of feeding was 5.92 (3.97) days after surgery. Sepsis (P=0.000), prematurity (P=0.000), type of anomaly (P=0.000), weight (P=0.000), time of defecation (P=0.000), duration of surgery (P=0.000), and volume of nasogastric tube secretions (P=0.000) had significant correlations with the time of onset of feeding, but gender (P=0.559) and heart disease (P=0.210) had no such correlation. Conclusions: Regardless of the neonates’ gender and the presence of cardiac anomalies, feeding can be started earlier in full-term and overweight infants. The amount of return secretions of the nasogastric tube and the type of surgery should be considered in making this decision.